Fiber composite needled filter material and preparation method thereof

By using fiber composite needle-punching filter material, high-temperature resistant polyester fiber and reinforced fiber, combined with modified nanocarbon fiber and other materials, the problem of deterioration of existing filter materials in high-temperature environments is solved, and higher high-temperature stability and service life are achieved.

CN119502495AActive Publication Date: 2025-02-25JIANGSU AOKAI ENVIRONMENTAL PROTECTION TECH CO LTD

Patent Information

Application Number
CN202411768000.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-02-25
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

The performance of existing fiber filters in high-temperature environments is deteriorated and it is impossible to effectively filter high-temperature gases.

Method used

The fiber composite needle-punched filter material is used, which consists of high-temperature resistant polyester fibers and reinforced fibers. The high-temperature performance of the filter material is improved by the use of modified nanocarbon fibers and polyphenylene sulfide fibers.

Benefits of technology

It significantly improves the stability and service life of fiber composite needle-punching filter material at high temperatures, and enhances its resistance to chemical corrosion such as acid and alkali.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of dust removal filter materials, in particular to a fiber composite needled filter material and a preparation method thereof. In order to enhance the high-temperature performance of the needle-punched filter material, a modified carbon fiber material is added into polyethylene glycol terephthalate; according to the preparation method disclosed by the invention, the surface of the nano carbon fiber is subjected to carboxylation treatment after being subjected to oxidation treatment, a fluorine element is introduced into the surface of the carbon fiber on the basis, and a structure similar to ethylene glycol terephthalate is further prepared on the surface of the carbon fiber; therefore, the compatibility and the bonding strength between the carbon nanofibers and the polyethylene terephthalate are greatly improved; meanwhile, the fluorine element introduced in the process can greatly improve the stability of the polyester fiber at high temperature and enhance the resistance of the polyester fiber to chemical erosion such as acid and alkali, so that the service life of the filter material in high-temperature flue gas is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of dust removal filter materials, in particular to a fiber composite needle-punched filter material and a preparation method thereof. Background Art

[0002] In recent years, with the development of my country's industry, the problem of air pollution caused by industry has also been increasingly valued. At present, among industrial pollution, atmospheric dust pollution accounts for a large proportion. The tiny dust generated by various industries will be suspended in the atmosphere for a long time, causing the decline of air quality and affecting human health. Therefore, composite fiber filter materials are often used in the industrial field to treat exhaust gas. Patent CN201611224888.2 discloses a manufacturing process for medium and low temperature filter materials, in which polyester is used as the main raw material. Polyester fiber has excellent mechanical properties, but in high temperature environments, especially in environments with temperatures exceeding 150°C, the performance will seriously deteriorate and cannot meet the filtering requirements of high temperature gases. Therefore, it is necessary to conduct research on this defect to meet market demand. Summary of the invention

[0003] The object of the present invention is to provide a fiber composite needle-punched filter material and a preparation method thereof, so as to solve the problems raised in the above background technology.

[0004] In order to solve the above technical problems, the present invention provides the following technical solutions: A fiber composite needle-punched filter material, having the following technical features: by weight, the fiber composite needle-punched filter material is composed of a base fabric and fiber layers covering the upper and lower surfaces of the base fabric; Wherein, in the fiber layer, the weight percentage of high temperature resistant polyester fiber is 60-85%, and the rest is reinforcing fiber; The reinforcing fiber is any one of polyphenylene sulfide fiber and PTFE fiber.

[0005] Furthermore, the high temperature resistant polyester fiber is composed of 45-65 parts of polyethylene terephthalate, 5-15 parts of modified carbon nanofibers, 0.08-0.15 parts of antioxidants, 0.3-0.45 parts of antistatic agents, and 0.1-0.2 parts of dispersants, by weight. Wherein, the antioxidant is any one of 2,5-di-tert-butylhydroquinone and N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine; the antistatic agent is potassium acetate; and the dispersant is stearic acid.

[0006] Furthermore, the base fabric is a PPS base fabric.

[0007] Furthermore, a method for preparing a fiber composite needle-punched filter material comprises the following steps: S1. Preparation of modified carbon nanofibers; S11. Disperse the nanocarbon fibers in concentrated sulfuric acid, heat to 80±5°C, add potassium persulfate, stir and react for 5-8h, cool to 10±5°C, add sodium nitrate and potassium permanganate, heat to 40±5°C, stir and react for 4-6h, centrifuge and separate the precipitate, wash the precipitate with hydrogen peroxide and dilute hydrochloric acid for 3-5 times, disperse the nanocarbon fibers again in deionized water, add monochloroacetic acid and sodium hydroxide, heat to 50±5°C, stir and react for 4-5h, centrifuge and separate the precipitate, and vacuum dry to constant weight to obtain carboxylated nanocarbon fibers; S12. Add 10-15% of the volume of propylene glycol to deionized water, mix for 5-10 minutes, then add sodium hydroxide, continue stirring for 2-15 minutes, and then add perfluoro-2-methyl-3-oxahexanoic acid dropwise under nitrogen atmosphere. Stir continuously during the addition. After the addition is completed, heat the mixture to 95±3°C, reflux for 2-8 hours, and then remove excess solvent by rotary evaporation. Wash the reaction product 1-3 times with deionized water at 3±2°C, and then evaporate to constant weight in vacuo to obtain a fluoroalcohol intermediate. S13. The carboxylated carbon nanofibers obtained in step S11 are dispersed in perfluorooctane, and dispersed under ultrasonic vibration for 25-60 minutes. Under nitrogen atmosphere protection, the fluoroalcohol intermediate obtained in step S12 is added, and the temperature is raised to 85±10°C. After stirring for 4-12 hours, the precipitation is separated by centrifugation, and washed 2-3 times with pure perfluorooctane. The dried product is dried at 110°C for 24 hours, and then dispersed in toluene again. After ultrasonic vibration treatment for 30-45 minutes, p-toluenesulfonic acid is added thereto. After mixing for 3-5 minutes, benzoic acid is added, and the temperature is raised to 110±5°C. After reacting for 1.5-8 hours, the precipitation is separated by centrifugation, and washed 2-3 times with toluene. The dried product is dried under vacuum to constant weight to obtain modified carbon nanofibers. S2. Preparation of high temperature resistant polyester fiber; S21. Mixing polyethylene terephthalate chips with modified nanocarbon fibers, heating to 230±10°C for premixing for 5-10 minutes, adding an antioxidant, an antistatic agent, and a dispersant, and continuing to mix for 3-5 minutes, extruding the chips to obtain a high temperature resistant polyester masterbatch; S22. The high temperature resistant polyester masterbatch is melt-spun to obtain a high temperature resistant polyester fiber; S3. Preparation of fiber composite needle-punched filter material; The high-temperature resistant polyester fiber and the reinforcing fiber are mixed in proportion and then combed and laid to form a fiber layer, and the fiber layer is respectively covered on the upper and lower surfaces of the base cloth. After needle punching, polytetrafluoroethylene emulsion is coated on the surface, and after drying, a fiber composite needle-punched filter material is formed.

[0008] Furthermore, in step S11, the mass ratio of the nano-carbon fibers, potassium persulfate, sodium nitrate and potassium permanganate is 1:(3-5):(1-5):(5-10) in parts by weight; The mass ratio of the nano-carbon fiber, monochloroacetic acid and sodium hydroxide is 1:(3-5):(4-5).

[0009] Furthermore, in step S12, the mass ratio of propylene glycol, sodium hydroxide and perfluoro-2-methyl-3-oxahexanoic acid is 10:(0.2-0.6):(10-95) in parts by weight.

[0010] Furthermore, in step S13, the mass ratio of the carboxylated carbon nanofiber to the fluoroalcohol intermediate is 1:(0.5-4) in parts by weight.

[0011] Furthermore, in step S13, the mass ratio of the carboxylated carbon nanofibers, p-toluenesulfonic acid, and benzoic acid is 1: (0.02-0.04): (0.5-5) in parts by weight.

[0012] Compared with the prior art, the beneficial effects achieved by the present invention are: In order to enhance the high temperature performance of the needle-punched filter material, the present invention improves the raw material of the filter material, and adds modified carbon fiber material to polyethylene terephthalate; In the process of preparing the modified carbon fiber material, the present invention first performs an oxidation treatment on the nano-carbon fiber, and uses the strong oxidizing ability of substances such as concentrated sulfuric acid and potassium permanganate to generate active groups such as epoxy groups on the surface of the nano-carbon fiber, and then uses raw materials such as monochloroacetic acid to further generate carboxyl groups on the surface of the nano-carbon fiber; On this basis, the present invention uses propylene glycol as a raw material, mixes it with perfluoro 2-methyl-3-oxahexanoic acid to react, thereby preparing a fluoroalcohol intermediate containing a large amount of fluorine element, and then mixes it with a carboxylated nano-carbon fiber with a carboxyl group on the surface, thereby introducing fluorine element and alcohol hydroxyl group on the surface of the nano-carbon fiber, and then further reacts with benzoic acid to generate a structure similar to ethylene terephthalate on the surface of the nano-carbon fiber, greatly increasing the compatibility and bonding strength between the nano-carbon fiber and polyethylene terephthalate; at the same time, the fluorine element introduced in this process can greatly improve the stability of the polyester fiber at high temperature, and enhance its resistance to chemical corrosion such as acid and alkali, thereby improving the service life in high-temperature flue gas. DETAILED DESCRIPTION

[0013] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0014] The base fabric used in this application is 1.5D*51mm woven, with a warp density of 150 yarns / 10cm and a weft density of 60 yarns / 10cm; The nanocarbon fibers used had a diameter × length of 100 nm × 20-200 μm and a density of 1.9 g / mL; The polyethylene terephthalate slices used were B2520 polyethylene terephthalate; The solid content of the polytetrafluoroethylene emulsion used was 28%; Example 1. A method for preparing a fiber composite needle-punched filter material, comprising the following steps: S1. Preparation of modified carbon nanofibers; S11. According to the weight ratio, 1 part of nano-carbon fiber is dispersed in 95 parts of concentrated sulfuric acid, the temperature is raised to 80°C, 4 parts of potassium persulfate are added, and the reaction is stirred for 5 hours, then the temperature is cooled to 5°C, 3 parts of sodium nitrate and 10 parts of potassium permanganate are added, the temperature is raised to 40°C, the reaction is stirred for 4 hours, and the precipitation is separated by centrifugation. The precipitation is washed 3 times with hydrogen peroxide and dilute hydrochloric acid respectively, and the nano-carbon fiber is dispersed again in 100 parts of deionized water, 3 parts of monochloroacetic acid and 4 parts of sodium hydroxide are added, the temperature is raised to 55°C, the reaction is stirred for 4 hours, the precipitation is separated by centrifugation, and vacuum dried to constant weight to obtain carboxylated nano-carbon fiber; S12. According to the weight ratio, 10 parts of propylene glycol were added with 10% of its volume of deionized water, mixed for 5 minutes, and then 0.3 parts of sodium hydroxide were added. After stirring for 10 minutes, 10 parts of perfluoro-2-methyl-3-oxahexanoic acid were added dropwise under nitrogen atmosphere, and stirring was continued during the addition. After the addition was completed, the mixture was heated to 98°C, refluxed for 6 hours, and then the excess solvent was removed by rotary evaporation. The reaction product was washed twice with deionized water at a temperature of 3°C, and then vacuum evaporated to constant weight to obtain a fluoroalcohol intermediate; S13. By weight, 1 part of the carboxylated carbon nanofiber obtained in step S11 was dispersed in perfluorooctane, and after ultrasonic dispersion for 45 minutes, under nitrogen atmosphere protection, 0.5 parts of the fluoroalcohol intermediate obtained in step S12 were added, the temperature was raised to 85°C, and the reaction was stirred for 8 hours. After centrifugation, the precipitation was washed twice with pure perfluorooctane, and the temperature was raised to 110°C and dried for 24 hours. The dried product was dispersed in toluene again, and after ultrasonic treatment for 30 minutes, 0.02 parts of p-toluenesulfonic acid were added thereto. After mixing for 4 minutes, 0.5 parts of benzoic acid were added, the temperature was raised to 110°C, and the reaction was continued for 4 hours. After the precipitation was centrifuged, it was washed twice with toluene, and vacuum dried to constant weight to obtain modified carbon nanofibers; S2. Preparation of high temperature resistant polyester fiber; S21. By weight, 50 parts of polyethylene terephthalate chips were mixed with 5 parts of modified nano-carbon fibers, and the mixture was heated to 240°C for premixing for 8 minutes, and then 0.15 parts of 2,5-di-tert-butylhydroquinone antioxidant, 0.3 parts of potassium acetate antistatic agent, and 0.2 parts of stearic acid dispersant were added. After mixing for 3 minutes, the chips were extruded to obtain high temperature resistant polyester masterbatch; S22. The high temperature resistant polyester masterbatch was melt-spun to obtain a high temperature resistant polyester fiber of 0.9D * 51mm; S3. Preparation of fiber composite needle-punched filter material; By weight, 8 parts of high-temperature resistant polyester fibers and 2 parts of 1.2D*51mm PPS reinforced fibers are mixed in proportion and then combed and laid to form a fiber layer. The fiber layers are then covered on the upper and lower surfaces of the base fabric respectively, and after needle-punching processing, polytetrafluoroethylene emulsion is coated on the surface, and then dried to form a fiber composite needle-punched filter material.

[0015] Example 2. A method for preparing a fiber composite needle-punched filter material, comprising the following steps: Compared with Example 1, this embodiment increases the amount of modified carbon fiber added in step S21; S1. Preparation of modified carbon nanofibers; S11. According to the weight ratio, 1 part of nano-carbon fiber is dispersed in 95 parts of concentrated sulfuric acid, the temperature is raised to 80°C, 4 parts of potassium persulfate are added, and the reaction is stirred for 5 hours, then the temperature is cooled to 5°C, 3 parts of sodium nitrate and 10 parts of potassium permanganate are added, the temperature is raised to 40°C, the reaction is stirred for 4 hours, and the precipitation is separated by centrifugation. The precipitation is washed 3 times with hydrogen peroxide and dilute hydrochloric acid respectively, and the nano-carbon fiber is dispersed again in 100 parts of deionized water, 3 parts of monochloroacetic acid and 4 parts of sodium hydroxide are added, the temperature is raised to 55°C, the reaction is stirred for 4 hours, the precipitation is separated by centrifugation, and vacuum dried to constant weight to obtain carboxylated nano-carbon fiber; S12. According to the weight ratio, 10 parts of propylene glycol were added with 10% of its volume of deionized water, mixed for 5 minutes, and then 0.3 parts of sodium hydroxide were added. After stirring for 10 minutes, 10 parts of perfluoro-2-methyl-3-oxahexanoic acid were added dropwise under nitrogen atmosphere, and stirring was continued during the addition. After the addition was completed, the mixture was heated to 98°C, refluxed for 6 hours, and then the excess solvent was removed by rotary evaporation. The reaction product was washed twice with deionized water at a temperature of 3°C, and then vacuum evaporated to constant weight to obtain a fluoroalcohol intermediate; S13. By weight, 1 part of the carboxylated carbon nanofiber obtained in step S11 was dispersed in perfluorooctane, and after ultrasonic dispersion for 45 minutes, under nitrogen atmosphere protection, 0.5 parts of the fluoroalcohol intermediate obtained in step S12 were added, the temperature was raised to 85°C, and the reaction was stirred for 8 hours. After centrifugation, the precipitation was washed twice with pure perfluorooctane, and the temperature was raised to 110°C and dried for 24 hours. The dried product was dispersed in toluene again, and after ultrasonic treatment for 30 minutes, 0.02 parts of p-toluenesulfonic acid were added thereto. After mixing for 4 minutes, 0.5 parts of benzoic acid were added, the temperature was raised to 110°C, and the reaction was continued for 4 hours. After the precipitation was centrifuged, it was washed twice with toluene, and vacuum dried to constant weight to obtain modified carbon nanofibers; S2. Preparation of high temperature resistant polyester fiber; S21. By weight, 50 parts of polyethylene terephthalate chips were mixed with 15 parts of modified nano-carbon fibers, and the mixture was heated to 240° C. and pre-mixed for 8 minutes. Then, 0.15 parts of 2,5-di-tert-butylhydroquinone antioxidant, 0.3 parts of potassium acetate antistatic agent, and 0.2 parts of stearic acid dispersant were added. After mixing for 3 minutes, the chips were extruded to obtain high temperature resistant polyester masterbatch. S22. The high temperature resistant polyester masterbatch was melt-spun to obtain a high temperature resistant polyester fiber of 0.9D * 51mm; S3. Preparation of fiber composite needle-punched filter material; By weight, 8 parts of high-temperature resistant polyester fibers and 2 parts of 1.2D*51mm PPS reinforced fibers are mixed in proportion and then combed and laid to form a fiber layer. The fiber layers are then covered on the upper and lower surfaces of the base fabric respectively, and after needle-punching processing, polytetrafluoroethylene emulsion is coated on the surface, and then dried to form a fiber composite needle-punched filter material.

[0016] Example 3. A method for preparing a fiber composite needle-punched filter material, comprising the following steps: Compared with Example 1, this example increases the amount of fluoro-2-methyl-3-oxahexanoic acid added in step S12; S1. Preparation of modified carbon nanofibers; S11. According to the weight ratio, 1 part of nano-carbon fiber is dispersed in 95 parts of concentrated sulfuric acid, the temperature is raised to 80°C, 4 parts of potassium persulfate are added, and the reaction is stirred for 5 hours, then the temperature is cooled to 5°C, 3 parts of sodium nitrate and 10 parts of potassium permanganate are added, the temperature is raised to 40°C, the reaction is stirred for 4 hours, and the precipitation is separated by centrifugation. The precipitation is washed 3 times with hydrogen peroxide and dilute hydrochloric acid respectively, and the nano-carbon fiber is dispersed again in 100 parts of deionized water, 3 parts of monochloroacetic acid and 4 parts of sodium hydroxide are added, the temperature is raised to 55°C, the reaction is stirred for 4 hours, the precipitation is separated by centrifugation, and vacuum dried to constant weight to obtain carboxylated nano-carbon fiber; S12. According to the weight ratio, 10% of the volume of deionized water was added to 10 parts of propylene glycol, and 0.3 parts of sodium hydroxide was added after mixing for 5 minutes. After stirring and mixing for 10 minutes, 95 parts of perfluoro-2-methyl-3-oxahexanoic acid were added dropwise under nitrogen atmosphere, and stirring was continued during the addition. After the addition was completed, the mixture was heated to 98°C, refluxed for 6 hours, and the excess solvent was removed by rotary evaporation. The reaction product was washed twice with deionized water at a temperature of 3°C, and then evaporated to constant weight in vacuo to obtain a fluoroalcohol intermediate; S13. By weight, 1 part of the carboxylated carbon nanofiber obtained in step S11 was dispersed in perfluorooctane, and after ultrasonic dispersion for 45 minutes, under nitrogen atmosphere protection, 0.5 parts of the fluoroalcohol intermediate obtained in step S12 were added, the temperature was raised to 85°C, and the reaction was stirred for 8 hours. After centrifugation, the precipitation was washed twice with pure perfluorooctane, and the temperature was raised to 110°C and dried for 24 hours. The dried product was dispersed in toluene again, and after ultrasonic treatment for 30 minutes, 0.02 parts of p-toluenesulfonic acid were added thereto. After mixing for 4 minutes, 0.5 parts of benzoic acid were added, the temperature was raised to 110°C, and the reaction was continued for 4 hours. After the precipitation was centrifuged, it was washed twice with toluene, and vacuum dried to constant weight to obtain modified carbon nanofibers; S2. Preparation of high temperature resistant polyester fiber; S21. By weight, 50 parts of polyethylene terephthalate chips were mixed with 5 parts of modified nano-carbon fibers, and the mixture was heated to 240°C for premixing for 8 minutes, and then 0.15 parts of 2,5-di-tert-butylhydroquinone antioxidant, 0.3 parts of potassium acetate antistatic agent, and 0.2 parts of stearic acid dispersant were added. After mixing for 3 minutes, the chips were extruded to obtain high temperature resistant polyester masterbatch; S22. The high temperature resistant polyester masterbatch was melt-spun to obtain a high temperature resistant polyester fiber of 0.9D * 51mm; S3. Preparation of fiber composite needle-punched filter material; By weight, 8 parts of high-temperature resistant polyester fibers and 2 parts of 1.2D*51mm PPS reinforced fibers are mixed in proportion and then combed and laid to form a fiber layer. The fiber layers are then covered on the upper and lower surfaces of the base fabric respectively, and after needle-punching processing, polytetrafluoroethylene emulsion is coated on the surface, and then dried to form a fiber composite needle-punched filter material.

[0017] Example 4. A method for preparing a fiber composite needle-punched filter material, comprising the following steps: Compared with Example 1, this example increases the amount of fluoroalcohol intermediate added in step S13; S1. Preparation of modified carbon nanofibers; S11. According to the weight ratio, 1 part of nano-carbon fiber is dispersed in 95 parts of concentrated sulfuric acid, the temperature is raised to 80°C, 4 parts of potassium persulfate are added, and the reaction is stirred for 5 hours, then the temperature is cooled to 5°C, 3 parts of sodium nitrate and 10 parts of potassium permanganate are added, the temperature is raised to 40°C, the reaction is stirred for 4 hours, and the precipitation is separated by centrifugation. The precipitation is washed 3 times with hydrogen peroxide and dilute hydrochloric acid respectively, and the nano-carbon fiber is dispersed again in 100 parts of deionized water, 3 parts of monochloroacetic acid and 4 parts of sodium hydroxide are added, the temperature is raised to 55°C, the reaction is stirred for 4 hours, the precipitation is separated by centrifugation, and vacuum dried to constant weight to obtain carboxylated nano-carbon fiber; S12. According to the weight ratio, 10 parts of propylene glycol were added with 10% of its volume of deionized water, mixed for 5 minutes, and then 0.3 parts of sodium hydroxide were added. After stirring for 10 minutes, 10 parts of perfluoro-2-methyl-3-oxahexanoic acid were added dropwise under nitrogen atmosphere, and stirring was continued during the addition. After the addition was completed, the mixture was heated to 98°C, refluxed for 6 hours, and then the excess solvent was removed by rotary evaporation. The reaction product was washed twice with deionized water at a temperature of 3°C, and then vacuum evaporated to constant weight to obtain a fluoroalcohol intermediate; S13. By weight, disperse 1 part of the carboxylated carbon nanofiber obtained in step S11 into perfluorooctane, disperse under ultrasonic vibration for 45 minutes, protect under nitrogen atmosphere, add 4 parts of the fluoroalcohol intermediate obtained in step S12, heat to 85°C, stir to react for 8 hours, centrifuge to separate the precipitate, wash twice with pure perfluorooctane, heat to 110°C and dry for 24 hours, disperse the dried product again in toluene, treat with ultrasonic vibration for 30 minutes, add 0.02 parts of p-toluenesulfonic acid, continue mixing for 4 minutes, add 0.5 parts of benzoic acid, heat to 110°C, react for 4 hours, centrifuge to separate the precipitate, wash twice with toluene, and vacuum dry to constant weight to obtain modified carbon nanofiber; S2. Preparation of high temperature resistant polyester fiber; S21. By weight, 50 parts of polyethylene terephthalate chips were mixed with 5 parts of modified nano-carbon fibers, and the mixture was heated to 240°C for premixing for 8 minutes, and then 0.15 parts of 2,5-di-tert-butylhydroquinone antioxidant, 0.3 parts of potassium acetate antistatic agent, and 0.2 parts of stearic acid dispersant were added. After mixing for 3 minutes, the chips were extruded to obtain high temperature resistant polyester masterbatch; S22. The high temperature resistant polyester masterbatch was melt-spun to obtain a high temperature resistant polyester fiber of 0.9D * 51mm; S3. Preparation of fiber composite needle-punched filter material; By weight, 8 parts of high-temperature resistant polyester fibers and 2 parts of 1.2D*51mm PPS reinforced fibers are mixed in proportion and then combed and laid to form a fiber layer. The fiber layers are then covered on the upper and lower surfaces of the base fabric respectively, and after needle-punching processing, polytetrafluoroethylene emulsion is coated on the surface, and then dried to form a fiber composite needle-punched filter material.

[0018] Example 5. A method for preparing a fiber composite needle-punched filter material, comprising the following steps: Compared with Example 1, this example increases the amount of benzoic acid added in step S12; S1. Preparation of modified carbon nanofibers; S11. According to the weight ratio, 1 part of nano-carbon fiber is dispersed in 95 parts of concentrated sulfuric acid, the temperature is raised to 80°C, 4 parts of potassium persulfate are added, and the reaction is stirred for 5 hours, then the temperature is cooled to 5°C, 3 parts of sodium nitrate and 10 parts of potassium permanganate are added, the temperature is raised to 40°C, the reaction is stirred for 4 hours, and the precipitation is separated by centrifugation. The precipitation is washed 3 times with hydrogen peroxide and dilute hydrochloric acid respectively, and the nano-carbon fiber is dispersed again in 100 parts of deionized water, 3 parts of monochloroacetic acid and 4 parts of sodium hydroxide are added, the temperature is raised to 55°C, the reaction is stirred for 4 hours, the precipitation is separated by centrifugation, and vacuum dried to constant weight to obtain carboxylated nano-carbon fiber; S12. According to the weight ratio, 10 parts of propylene glycol were added with 10% of its volume of deionized water, mixed for 5 minutes, and then 0.3 parts of sodium hydroxide were added. After stirring for 10 minutes, 10 parts of perfluoro-2-methyl-3-oxahexanoic acid were added dropwise under nitrogen atmosphere, and stirring was continued during the addition. After the addition was completed, the mixture was heated to 98°C, refluxed for 6 hours, and then the excess solvent was removed by rotary evaporation. The reaction product was washed twice with deionized water at a temperature of 3°C, and then vacuum evaporated to constant weight to obtain a fluoroalcohol intermediate; S13. By weight, 1 part of the carboxylated carbon nanofiber obtained in step S11 was dispersed in perfluorooctane, and after ultrasonic dispersion for 45 minutes, under nitrogen atmosphere protection, 0.5 parts of the fluoroalcohol intermediate obtained in step S12 was added, the temperature was raised to 85°C, and the reaction was stirred for 8 hours. After centrifugation, the precipitation was washed twice with pure perfluorooctane, and the temperature was raised to 110°C and dried for 24 hours. The dried product was dispersed in toluene again, and after ultrasonic treatment for 30 minutes, 0.02 parts of p-toluenesulfonic acid was added thereto. After mixing for 4 minutes, 5 parts of benzoic acid were added, the temperature was raised to 110°C, and the reaction was continued for 4 hours. After the precipitation was centrifuged, it was washed twice with toluene, and vacuum dried to constant weight to obtain modified carbon nanofibers; S2. Preparation of high temperature resistant polyester fiber; S21. By weight, 50 parts of polyethylene terephthalate chips were mixed with 5 parts of modified nano-carbon fibers, and the mixture was heated to 240°C for premixing for 8 minutes, and then 0.15 parts of 2,5-di-tert-butylhydroquinone antioxidant, 0.3 parts of potassium acetate antistatic agent, and 0.2 parts of stearic acid dispersant were added. After mixing for 3 minutes, the chips were extruded to obtain high temperature resistant polyester masterbatch; S22. The high temperature resistant polyester masterbatch was melt-spun to obtain a high temperature resistant polyester fiber of 0.9D * 51mm; S3. Preparation of fiber composite needle-punched filter material; By weight, 8 parts of high-temperature resistant polyester fibers and 2 parts of 1.2D*51mm PPS reinforced fibers are mixed in proportion and then combed and laid to form a fiber layer. The fiber layers are then covered on the upper and lower surfaces of the base fabric respectively, and after needle-punching processing, polytetrafluoroethylene emulsion is coated on the surface, and then dried to form a fiber composite needle-punched filter material.

[0019] Comparative Example 1. A method for preparing a fiber composite needle-punched filter material, comprising the following steps: Compared with Example 1, this comparative example only used ordinary carbon nanofibers; S1. Preparation of high temperature resistant polyester fiber; S11. By weight, 50 parts of polyethylene terephthalate chips were mixed with 5 parts of modified nano-carbon fibers, and the mixture was heated to 240°C for premixing for 8 minutes, and then 0.15 parts of 2,5-di-tert-butylhydroquinone antioxidant, 0.3 parts of potassium acetate antistatic agent, and 0.2 parts of stearic acid dispersant were added. After mixing for 3 minutes, the chips were extruded to obtain high temperature resistant polyester masterbatch; S12. The high temperature resistant polyester masterbatch was melt-spun to obtain a high temperature resistant polyester fiber of 0.9D * 51mm; S2. Preparation of fiber composite needle-punched filter material; By weight, 8 parts of high-temperature resistant polyester fibers and 2 parts of 1.2D*51mm PPS reinforced fibers are mixed in proportion and then combed and laid to form a fiber layer. The fiber layers are then covered on the upper and lower surfaces of the base fabric respectively, and after needle-punching processing, polytetrafluoroethylene emulsion is coated on the surface, and then dried to form a fiber composite needle-punched filter material.

[0020] Detection: The fiber composite needle-punched filter materials prepared in Examples 1-5 and Comparative Example 1 were prepared into a pattern with a thickness of 1.5±0.5 mm; The gram weight of the samples prepared in Examples 1-5 and Comparative Example 1 was tested according to GB / T 24218.1-2009; the air permeability of the samples prepared in Examples 1-5 and Comparative Example 1 was tested according to GB / T5453-1997; the breaking strength and elongation of the samples prepared in Examples 1-5 and Comparative Example 1 were tested according to GB / T 24218.3-2010; After the samples prepared in Examples 1-5 and Comparative Example 1 were placed in an environment at a temperature of 160°C for 30 days, the breaking strength was tested again. The test results are shown in the following table;

[0021] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A fiber composite needle-punched filter material, characterized in that: The fiber composite needle-punched filter material is composed of a base fabric and fiber layers covering the upper and lower surfaces of the base fabric by weight; Wherein, in the fiber layer, the weight percentage of high temperature resistant polyester fiber is 60-85%, and the rest is reinforcing fiber; The reinforcing fiber is any one of polyphenylene sulfide fiber and PTFE fiber; The high temperature resistant polyester fiber is composed of 45-65 parts of polyethylene terephthalate, 5-15 parts of modified carbon nanofibers, 0.08-0.15 parts of antioxidants, 0.3-0.45 parts of antistatic agents, and 0.1-0.2 parts of dispersants by weight; Wherein, the antioxidant is any one of 2,5-di-tert-butylhydroquinone and N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine; the antistatic agent is potassium acetate; and the dispersant is stearic acid.

2. The fiber composite needle-punched filter material according to claim 1, characterized in that: The base fabric is a PPS base fabric.

3. A method for preparing the fiber composite needle-punched filter material according to any one of claims 1 to 2, characterized in that: The following steps are involved: S1. Preparation of modified carbon nanofibers; S11. Disperse the nanocarbon fibers in concentrated sulfuric acid, heat to 80±5°C, add potassium persulfate, stir and react for 5-8h, cool to 10±5°C, add sodium nitrate and potassium permanganate, heat to 40±5°C, stir and react for 4-6h, centrifuge and separate the precipitate, wash the precipitate with hydrogen peroxide and dilute hydrochloric acid for 3-5 times, disperse the nanocarbon fibers again in deionized water, add monochloroacetic acid and sodium hydroxide, heat to 50±5°C, stir and react for 4-5h, centrifuge and separate the precipitate, and vacuum dry to constant weight to obtain carboxylated nanocarbon fibers; S12. Add 10-15% of the volume of propylene glycol to deionized water, mix for 5-10 minutes, then add sodium hydroxide, continue stirring for 2-15 minutes, and then add perfluoro-2-methyl-3-oxahexanoic acid dropwise under nitrogen atmosphere. Stir continuously during the addition. After the addition is completed, heat the mixture to 95±3°C, reflux for 2-8 hours, and then remove excess solvent by rotary evaporation. Wash the reaction product 1-3 times with deionized water at 3±2°C, and then evaporate to constant weight in vacuo to obtain a fluoroalcohol intermediate. S13. The carboxylated carbon nanofibers obtained in step S11 are dispersed in perfluorooctane, and dispersed under ultrasonic vibration for 25-60 minutes. Under nitrogen atmosphere protection, the fluoroalcohol intermediate obtained in step S12 is added, and the temperature is raised to 85±10°C. After stirring for 4-12 hours, the precipitation is separated by centrifugation, and washed 2-3 times with pure perfluorooctane. The dried product is dried at 110°C for 24 hours, and then dispersed in toluene again. After ultrasonic vibration treatment for 30-45 minutes, p-toluenesulfonic acid is added thereto. After mixing for 3-5 minutes, benzoic acid is added, and the temperature is raised to 110±5°C. After reacting for 1.5-8 hours, the precipitation is separated by centrifugation, and washed 2-3 times with toluene. The dried product is dried under vacuum to constant weight to obtain modified carbon nanofibers. S2. Preparation of high temperature resistant polyester fiber; S21. Mixing polyethylene terephthalate chips with modified nanocarbon fibers, heating to 230±10°C for premixing for 5-10 minutes, adding an antioxidant, an antistatic agent, and a dispersant, and continuing to mix for 3-5 minutes, extruding the chips to obtain a high temperature resistant polyester masterbatch; S22. The high temperature resistant polyester masterbatch is melt-spun to obtain a high temperature resistant polyester fiber; S3. Preparation of fiber composite needle-punched filter material; The high-temperature resistant polyester fiber and the reinforcing fiber are mixed in proportion and then combed and laid to form a fiber layer, and the fiber layer is respectively covered on the upper and lower surfaces of the base cloth. After needle punching, polytetrafluoroethylene emulsion is coated on the surface, and after drying, a fiber composite needle-punched filter material is formed.

4. The method for preparing a fiber composite needle-punched filter material according to claim 3, characterized in that: In step S11, the mass ratio of the nano-carbon fibers, potassium persulfate, sodium nitrate and potassium permanganate is 1:(3-5):(1-5):(5-10) in parts by weight; The mass ratio of the nano-carbon fiber, monochloroacetic acid and sodium hydroxide is 1:(3-5):(4-5).

5. The method for preparing a fiber composite needle-punched filter material according to claim 3, characterized in that: In step S12, the mass ratio of propylene glycol, sodium hydroxide and perfluoro-2-methyl-3-oxahexanoic acid is 10:(0.2-0.6):(10-95) in parts by weight.

6. The method for preparing a fiber composite needle-punched filter material according to claim 3, characterized in that: In step S13, the mass ratio of the carboxylated carbon nanofiber to the fluoroalcohol intermediate is 1:(0.5-4) in parts by weight.

7. The method for preparing a fiber composite needle-punched filter material according to claim 3, characterized in that: In step S13, the mass ratio of the carboxylated carbon nanofibers, p-toluenesulfonic acid, and benzoic acid is 1: (0.02-0.04): (0.5-5) in parts by weight.

Citation Information

Patent Citations

  • A manufacturing process for medium and low temperature filter media

    CN106811982B

  • Preparation method of nano fiber-needling PTFE base cloth filter material

    CN106149206A

  • Antibacterial sportswear fabric

    CN111114038A

  • Degradable protective clothing and manufacturing method thereof

    CN116636667A

  • Carbon fiber for reinforcing thermoplastic resin

    JP2006077334A

Cited By

  • High-temperature-resistant high-precision filter material for dust removal filter cartridge and preparation method thereof

    CN121671111A